1984
DOI: 10.1177/105345128402000213
|View full text |Cite
|
Sign up to set email alerts
|

College Teachers' Expectations of LD Students

Abstract: University teachers hold negative academic expectations for LD students and are pessimistic about their ability to teach them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 1 publication
1
17
1
Order By: Relevance
“…Faculty responding to questionnaires in several states reveal limited knowledge of the nature and needs of students with disabilities and available services. Minner & Prater (1984) found in a study of faculty expectations that faculty reacted more negatively to students with a learning disabilities label. Researchers concluded that such stereotypes may hinder a student's success in the classroom.…”
Section: Susan B Asselinmentioning
confidence: 90%
“…Faculty responding to questionnaires in several states reveal limited knowledge of the nature and needs of students with disabilities and available services. Minner & Prater (1984) found in a study of faculty expectations that faculty reacted more negatively to students with a learning disabilities label. Researchers concluded that such stereotypes may hinder a student's success in the classroom.…”
Section: Susan B Asselinmentioning
confidence: 90%
“…The present findings do raise the possibility that faculty's academic expectations for students with learning disabilities may be unduly influenced by the disability label. As Minner and Prater (1984) pointed out, this could be especially damaging at the university level, where studentteacher interaction is often limited, thus making alterations in one's perceptions more difficult. Whether conscious or unconscious, misconceptions or prejudicial attitudes may create barriers to the pursuit of certain careers or result in unequal opportunities.…”
Section: Summary and Implicationsmentioning
confidence: 96%
“…The assessment of attitudes toward postsecondary students with learning disabilities has been proposed by a number of researchers (Miller, McKinley, & Ryan, 1979;Minner & Prater, 1984;Vogel, 1982;Vogel & Adelman, 1980). Minner and Prater found that the initial expectations of college faculty toward students with LD were negative.…”
Section: Attitudinalmentioning
confidence: 99%